Analisa Pengalaman Pengguna Pada Website SION (Sistem Informasi Online) ITB STIKOM Bali Menggunakan Metode User Experience Questionnaire (UEQ) - I Nyoman Yuda Sugiantara; I Made Bagus Mirandika Nugraha; Griffed Estonia Menanti; Joyce Joyce; Yusakh Hasudungan Lumingas; I Made Pradipta; Ida Ayu Mirah Cahya Dewi; Ni Kadek Tasya Novita Devi (STEKOM PRESS, 2024)
SION (Sistem Informasi Online) ITB STIKOM Bali is a platform used by students and lecturers to support administrative and academic processes on campus. This research examines how the user experience (UX) level of SION can enhance the quality of services provided by the system. The purpose of this study is to measure user satisfaction with the user experience quality. The study uses the User Experience Questionnaire (UEQ) method, which includes six rating scales: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. The UEQ method also offers analytic tools that can be downloaded from its official website. Respondents in this study consisted of 75 people from a population of 248. The results of the UEQ analysis show positive evaluations across all aspects, with the following detailed scores: attractiveness received a score of 1.37, perspicuity 1.34, efficiency 1.16, dependability 1.21, stimulation 1.16, and novelty 0.87.